(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The multidisciplinary discipline of artificial intelligence integrates information theory, cloud computing, big data, and machine learning. The main benefit of machine learning is that it builds on past experience, allowing machines to learn from their mistakes and make error-free future predictions. This type of decision-making process is used in a number of industries, including social media, healthcare, finance, and others. The volume of data in big data and cloud computing is growing and sustainable, and machine learning helps process it with less power usage. Because the future Massive Internet of Things (MIoT), one of the pillars of the 5G/6G network factory, integrates AI and IoT support with the communication infrastructure, it is possible to support the next generation of smart grid by providing the platform that integrates these elements. This results in a multitenant system. Fast advancements in machine learning, deep learning, and artificial intelligence (AI) will improve outcomes for applications in the future. The developments and difficulties around artificial intelligence are covered in this paper.